1989
DOI: 10.1128/mcb.9.9.3919-3930.1989
|View full text |Cite
|
Sign up to set email alerts
|

hsp82 Is an Essential Protein That Is Required in Higher Concentrations for Growth of Cells at Higher Temperatures

Abstract: hsp82 is one of the most highly conserved and abundantly synthesized heat shock proteins of eucaryotic cells. The yeast Saccharomyces cerevisiae contains two closely related genes in the HSP82 gene family. HSC82 was expressed constitutively at a very high level and was moderately induced by high temperatures. HSP82 was expressed constitutively at a much lower level and was more strongly induced by heat. Site-directed disruption mutations were produced in both genes. Cells homozygous for both mutations did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(40 citation statements)
references
References 47 publications
1
34
0
5
Order By: Relevance
“… Felsheim and Das (1992) reported the differential expression of HSP83 member genes in response to heat stress and photoperiod duration in cotyledons. Disruption of genes encoding HSP83 has been shown to have detrimental effects on the growth and survival in yeast at high temperature ( Borkovich et al, 1989 ). Our results also agree with the above study and we can conclude that heat shock proteins also have an essential role in wheat during heat stress.…”
Section: Discussionmentioning
confidence: 99%
“… Felsheim and Das (1992) reported the differential expression of HSP83 member genes in response to heat stress and photoperiod duration in cotyledons. Disruption of genes encoding HSP83 has been shown to have detrimental effects on the growth and survival in yeast at high temperature ( Borkovich et al, 1989 ). Our results also agree with the above study and we can conclude that heat shock proteins also have an essential role in wheat during heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…In the unicellular eukaryote Saccharomyces cerevisiae ( S. cerevisiae ), genome-wide studies suggested that up to 10% of all proteins are directly or indirectly dependent on Hsp90 for function [ 26 , 27 ]. S. cerevisiae possesses two cytosolic Hsp90 isoforms encoded by separate genes, which arose from a genome duplication: the cognate Hsc82 and the stress-inducible Hsp82 [ 28 ]. Under non-stress conditions, Hsc82 is expressed at tenfold higher levels than Hsp82 [ 28 ].…”
Section: Hsp90 Homologs and Paralogsmentioning
confidence: 99%
“…Human Hsp90 shares 50% sequence similarity with the Escherichia coli HtpG [ 8 ]. Simple metazoans, such as Caenorhabditis elegans (HSP-90, previously DAF-21) and Drosophila melanogaster (Hps83), have only one cytosolic Hsp90, whereas the yeast S. cerevisiae [ 9 ] has two, includin the constitutive Hsc82 and the heat-inducible Hsp82 [ 10 , 11 , 12 ]. Despite their 97% amino acid identity [ 10 ], there are differences in client preference as well as in their sensitivity to Hsp90 inhibitors [ 13 ].…”
Section: The Hsp90 Chaperonementioning
confidence: 99%